An appraisal of the models for the prediction of compressive strength of thermally damaged self-compacting concrete. (2022) - Ahmad, Subhan; Umar, Arshad; Masood, Amjad
Abstract: Self-compacting concrete (SCC) mixtures were prepared using 5% and 10% micro silica (MS). Fresh properties are measured using slump flow with T500 time, L-box ratio and V-funnel time. SCC with lower MS content yielded better workability properties. Hardened SCC samples were heated up to 200 °C, 400 °C and 600 °C in an electric furnace and allowed to cool naturally. The compressive strength of unheated and heated samples after cooling was determined. It was observed that up to 400 °C, SCC with 10% MS suffered higher strength loss than SCC with 5% MS. For 600 °C, strength loss for both the SCC mixtures was approximately equal. Furthermore, residual compressive strength of one hundred seven SCC specimens (including eighteen of this study) was predicted using the residual compressive strength models available in the literature. Though the available models were proposed for normal vibrated concrete (NVC), statistical analysis showed that they could also be used for SCC.